Strategies for conservation of highland ecosystem in Pulinguí San Pablo and Chorrera Mirador, Ecuador - Lozano, Patricio; Armas, Aracely; Machado, Verónica (Enfoque UTE, 2016)
To drive conservation processes and sustainable use of an ecosystem implies, on the one hand, the understanding of the territory as a socio-ecosystem, and on the other hand, the application of the ecosystemic approach. For this reason, this is a tool that contributes to the highland ecosystem management of the communities Pulinguí San Pablo and Chorrera Mirador. This process was based on the socio-ecosystem characterization, determination of conservation elements and formulation of conservation and use of sustainable strategies. Data show that 186 habitants live in these socio-ecosystem and mainly benefit from three types of ecosystemic services: supply, regulation and cultural, carrying out agricultural, livestock and touristic activities. These settlements exert a moderated anthropic pressure in the socio-ecosystem due to the fact that only 98,65 hectares (out of 4567,20 hectares) are used for these activities. This is reflected in the state of the identified conservation elements that, evaluated according to their size, condition and landscaping context, obtained a mean of 3,3/4,0 (points) which means that they are in a decay process, nonetheless, their impacts may be diminished using established and executed strategies by local populations.